A COMPARATIVE ANALYSIS OF THE APPLICATION OF CROSS CULTURAL PRACTICES MODEL BETWEEN PATIENTS SEEKING TREATMENT IN WESTERN MEDICINE AND TRADITIONAL ASIAN MEDICINE - Amir Lukman Bin Abd Rahman; Nur Afifah Diyanah Shaharudin; Amirah Athirah Amir Yazid; Anis Shahira Bazlan (Journal of Islamic, Social, Economics and Development, 2022)
The usage of Traditional Asian medicine has been acknowledged in complementingit with western modern medicine especially in Malaysia. Therefore, this study aimed to assessthe views on the comparison of the application of cross-cultural practices model betweenpatients seeking Western medicine and Traditional Asian medicine treatments among Malay,Chinese and Indian. A semi-structured interview was conducted among six patients receivingWestern medical treatments and Traditional Asian medical treatments. Data from the interviewwere analysed through three types of practices from Lawrence’s (2004) model for crossculturalpractices in comprehending the patients’ perspectives on both treatments. Results ofthe study showed that patients who had received treatments from Western medicine andTraditional Asian medicine agreed that both medications were effective in treating theirillnesses. Moreover, the decisions to have chosen such treatments were influenced by theirfamily members, friends’ recommendations, and visitations from the medical institutions.Factors such as the the prescription of medication, daily supplements and procedure of thetreatment were the major causes in deciding the chosen treatment. Given that different races inMalaysia gave positive feedbacks on both types of treatments, this suggests medicalpractitioners and authorities to boost their strategies in the incorporation of traditional andmodern medicines as aligned with the Malaysia’s Traditional and Complementary Blueprint2018-2022.